State Responsibility in the Case of Forest Fires in Central Kalimantan as the Embodiment of a Welfare-Legal State - Tyas Arganing Dini; Trianah Sofiani; Eky Fallah Septiani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This research was motivated by the forest fires in Central Kalimantan which were getting worse. The losses experienced by local communities as a result of forest fires have brought the concept of state responsibility into question again. This research aims to find out whether there is neglect of forest fires which causes constitutional rights to have an impact on citizens. As a state, welfare law has not been realized because there is neglect and lack of fulfillment of constitutional rights from the state. Therefore, this research discusses the state's responsibility for forest fires in Central Kalimantan as an embodiment of a welfare state. The aim of this research is to analyze why the state ignored the forest fires in Central Kalimantan and to analyze the implications for the constitutional rights of citizens regarding the state ignoring the forest fires in Central Kalimantan.This research method is normative juridical research using a statutory approach and a conceptual approach. with the type of technique for collecting legal materials with documentation studies with an inventory of statutory regulations. The legal material analysis technique uses prescriptive analysis.The results of the research show that responsibility for forest fires in Indonesia, especially in Central Kalimantan, has been regulated in the 1945 Constitution, but there is still a disregard for the human rights of citizens which results in the community's constitutional rights not being fulfilled and the government not being optimal or weak, which causes forest fires to continue to occur. -continuously. Implications for the constitutional rights of citizens due to neglect by the state in forest fires in Central Kalimantan, the occurrence of forest fires in Central Kalimantan has resulted in the community's constitutional rights not being fulfilled and the absence of laws and regulations that regulate it, so this provides a gap for parties or individuals -certain individuals to carry out arson, as well as overlapping institutions dealing with forest fires in Central Kalimantan.